Про класичну електродинамiку Максвелла–Лоренца, проблему iнерцiї електрона та фейнманiвську парадигму власного часу - Prykarpatsky, A. K.; Bogolubov, Jr., N. N. (Publishing house "Academperiodika", 2019)
The classical Maxwell electromagnetic field and the Lorentz-type force equations are rederived in the framework of the Feynman proper time paradigm and the related vacuum field theory approach. The classical Ampere law origin is rederived, and its relationship with the Feynman proper time paradigm is discussed. The electron inertia problem is analyzed in detail within the Lagrangian and Hamiltonian formalisms and the related pressure-energy compensation principle of stochastic electrodynamics. The modified Abraham–Lorentz damping radiation force is derived, and the electromagnetic electron mass origin is argued.